The spatial organization of sequences involved in initiation and termination of eukaryotic DNA replication. - Cook, P; Lang, J (1984)
Nuclear DNA is looped by attachment to a matrix or cage. As this cage is the site of DNA synthesis, sequences in the loops must attach before they are replicated. We have tested whether sequences which initiate replication are usually out in the loop and attach only during S phase or whether they are attached but quiescent during most of the cell-cycle. Sequences which permit plasmids to replicate autonomously in yeast cells (ARS's) are strong candidates for initiating sequences. Four different human ARS's all map remote from attachment points to the HeLa nuclear cage. In addition a potential terminus of replication is also remote from the cage. We conclude that sequences involved in initiation are usually out in the loop and that DNA synthesis is initiated by their attachment.